Genetic analysis for economic traits in wheat under salt affected soil - Kumar, Yogender; Sethi, Sudhir Kumar; Lamba, Ram Avatar Singh (Journal of Cereal Research, 2014)
A study was conducted to estimate the genetic variability, correlation and path coefficient analysis of economic traits in 27 wheat genotypes grown in randomized block design with three replications during rabi season 2012-13 at CCS HAU, Regional Research Station, Bawal (Haryana) under sodic soil condition. Significant differences were observed among the genotypes for all the 10 economic traits studied viz., plant height (cm), ear length (cm), number of tillers per meterrow, number of grains per spike, days to heading, days to maturity, 1000-grain weight (g), harvest index (%), biological yield (kg/plot) and grain yield (kg/plot). High phenotypic coefficients of variation was observed for grain yield (18.57) followed by number of tillers per meter row (18.44) and harvest index (17.30) while, genotypic coefficients of variation was highest in number of tillers per meter row (16.27) followed by grain yield (13.31) and number of grains per spike (13.26). The estimates of heritability varied from 41 per cent for biological yield to 95 per cent for days to heading whereas grain yield showed51 per cent heritability. High heritability coupled with high genetic advance as per cent of mean was observed for number of tillers per meter row, number of grains per spike, 1000-grain weight and ear length indicating the importance of these traits in selection and crop improvement. The genotypic correlation estimates showed significant positive association of grain yield with harvest index, biological yieldand number of tillers per meter row. Days to heading, harvest index and biological yield exhibited the highest positive direct effect on grain yield. Hence, these traits could be considered as suitable selection criteria for the development of high yielding wheat varieties under salt stress conditions.